Optimalisasi Kinerja Hukum Tata Negara Melalui Lembaga KPK Dalam Upaya Mengurangi Angka Korupsi: Analisis Implementasi Strategi Penegakan Hukum Di Indonesia - Kuswan Hadji; Anggita Lailatun N; Intan Nur A; Nanda Patmawati; Karmila Nuralifah K; Cut Faizal S; Shafira Aulia H (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This journal discusses the optimization of the performance of constitutional law through the Corruption Eradication Commission (KPK) in an effort to reduce corruption, by analyzing the implementation of law enforcement strategies in Indonesia. This research aims to identify the role of the KPK in reducing the number of corruptions, examine the correlation between the integrity of public officials and corruption crimes, and highlight the challenges and obstacles faced by the KPK in carrying out its duties and obligations as a corruption eradication agency. The research method used is descriptive qualitative which uses secondary data in the form of written literature such as journals, articles and laws that are collected, analyzed and concluded so as to get the final conclusion. The results showed that the KPK has an important role in reducing the number of corruption through various law enforcement strategies that have been implemented. In addition, the KPK needs strong political support to carry out its duties effectively. However, sometimes there is political uncertainty and even resistance from parties who have an interest in corruption. Despite these challenges, the KPK must continue to strive to carry out its duties professionally and transparently in an effort to eradicate corruption in Indonesia. Therefore, steps are needed to improve the performance and effectiveness of the KPK in reducing corruption in Indonesia.